Unraveling the stigma: a qualitative descriptive exploration of the relationship between culture, religion, and mental disorders in Saudi Arabia - Loujain Sharif; Rawan Babhair; Diana Alzahrani; Alanoud Abuladel; Amani Kabli; Raghad Alzahrani; Lujain Alghamdi; Alaa Mahsoon; Khalid Sharif; Ruba Alharazi; Rebecca Wright (BMC Psychology)
Abstract Background A lack of understanding about the needs of people in Middle Eastern and Islamic contexts living with mental health disorders, and their experiences of diagnosis-related social and personal stigma inhibits high-quality care. Methods This qualitative descriptive study, based in Saudi Arabia, used the Stigma Mitigating Conceptual Model to explore mental disorder-related stigma from the perspective of challenges and strategies connected to knowledge, attitudes and behaviours. Thirteen adults with mental health disorders completed semi-structured interviews, analysed using reflexive thematic analysis. Results Four major themes and nine subthemes pertaining to the impact of stigma on public and self/personal knowledge, attitudes, and behaviors were identified: (1) effects of the mental disorder on everyday life, (2) challenges, (3) overcoming the challenges, and (4) types of stigma experienced. Greater knowledge of mental health disorders promoted Islamic principles of compassion and support, while the absence of knowledge exacerbated public stigma and fears the individual is under the influence of the ‘Evil Eye’, or lacks prayers and devotion. Participant strategies to mitigate stigma include education, and more opportunities for those living with mental health disorders to share their stories. Conclusions Study findings provide nuance into the role of stigma in the context of cultural and religious factors in Saudi. These insights can be used to help tailor care and interventions to people from Middle Eastern contexts, as Western perspectives have predominantly driven mental health care.